EXPERIMENTAL STUDY ON INHIBITION OF S180 TUMOR CELLS BY AGRIMONIA PILOSA EXTRACT - Wang, Xian; Wang, Hongyan; Zhang, Canbin; Ke Zhang, Ke (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
We evaluated the in vitro and in vivo inhibition of S180 tumor cell growth of the water extract of Agrimoniapilosa. Inhibitory effect of Agrimonia pilosa on in vitro-cultured S180 cell proliferation was measured by MTT assay;mice model of transplanted tumor was established, after 8 days of continuous administration, the tumors wereremoved, weighed, and compared with the control group, and the in vivo anti-tumor effect of Agrimonia pilosa onmouse sarcoma S180 was compared using inhibition rate. The in vitro anti-tumor experiment indicated that theinhibition rate gradually increases with the increase of extract concentration and the extension of time, withIC50 175.64, 90.59, and 71.74 μg/ml at 24 h, 4 h, and 72 h respectively. In this study, the in vitro MTT assay wasused to determine the inhibitory effect of Agrimony pilosa water extract on S180 tumor cells, the method is simple,reliable, and practical; mice model of in vivo transplanted S180 tumor was established, which allowed directobservation of tumor inhibitory effect, and thus found out that the water extract of Agrimonia pilosa has inhibitoryeffect on S180 tumor cells.